Prevalence of gastrointestinal parasitic infestation in cattle and goat at Boalia upazilla in Rajshahi district of Bangladesh - Sarker, Chalantika; Akter, Maria; Kayser, Ashraful; Asgar, Md Ali; Mollah, Mohammad Lalmoddin (Asian Journal of Medical and Biological Research, 2021)
The study was conducted to determine the prevalence of gastrointestinal parasitic infestation in cattle and goat at Metro Livestock Office, Boalia in Rajshahi District for 22 weeks from 1st December, 2020 to 30th April, 2021. A total number of 240 animals were included in the study. The overall prevalence of helminthes infestation was recorded 70 % (168) under semi-intensive system. The trematodal infestations (Fasciola & Paramphistomum) were found in cattle 37.64% and 20% and in goat 21.29%, 18.06% respectively. The nematodal infestations (Ascaris and Trichuris) were found of 12.94% & 3.52% in cattle and 25.16% & 3.22% in goat respectively. The highest prevalence was recorded in goat 43.75% than cattle 26.25%. In case of cattle the highest prevalence rate was recorded in female 65.07% than the male 34.92% and in goat 55.23% and 44.76%. In breed wise susceptibilty of helminth parasite, cross bred 60.31% were comparatively have higher prevalence than local bred cattle 39.68% and in case of goat Black Bengal goat 45.71% was less susceptible to Gastrointestinal parasitic infestation than Jamunapari goat 54.28%. The study suggests that importance should be given to proper management, improved hygiene and regular deworming to prevent the parasitic infestation in cattle. Therefore, the results of this study will help to the veterinary practitioner’s and researchers for management of gastrointestinal parasitic infestation in this area. Asian J. Med. Biol. Res. 2021, 7 (4), 367-374